University Experience and the Academic Profession - Jesús Francisco Galaz Fontes (Universidad Autónoma de Baja California, 1999)
<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">The identification, recruitment and nurturing of future scholars is of vital importance for the renewal of the academic profession. This paper discusses the influence of the college experience on students' decisions to pursue an academic career. Taking into consideration the nature of academic work, it describes the personal qualities most suitable for such a work, as well as the impact the university experience has on them. After discussing the decision of becoming an academic as a vocational choice, the paper ends with some policy recommendations for institutions interested in identifying and supporting students with the potential for going successfully into the academic profession.